1997
DOI: 10.1007/bf01279564
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine inhibition of cytokinesis: effect on the phragmoplast cytoskeleton in livingTradescantia stamen hair cells

Abstract: Summary. The distribution of microtubules and actin microfilaments during caffeine-induced inhibition of cell plate formation has been studied in living Tradescantia stamen hair cells. Previous studies have shown that caffeine allows cell plate initiation but prevents its completion, resulting in binucleate cells. In the present study, confocal microscopy of cells microinjected with fluorescent brain tubufin or phalloidin, and cultured in the presence 5 mM caffeine, revealed that the initiation and early later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 41 publications
3
68
1
Order By: Relevance
“…We defined these phases in BY-2 cells based on the lateral expansion rate of the growing cell plate as determined by FluMOS, but our quantitative analyses of published data for Arabidopsis root cells revealed that they are consistent with the kinetics of cells in a tissue context. It is safe to hypothesize that the phases we identified coincide with those based on other cellular parameters, such as actin dynamics, sensitivity to caffeine (Valster and Hepler, 1997), and microtubule dynamics (Seguí-Simarro et al, 2008), although an exact correlation warrants experimental proof.…”
Section: Discussionmentioning
confidence: 99%
“…We defined these phases in BY-2 cells based on the lateral expansion rate of the growing cell plate as determined by FluMOS, but our quantitative analyses of published data for Arabidopsis root cells revealed that they are consistent with the kinetics of cells in a tissue context. It is safe to hypothesize that the phases we identified coincide with those based on other cellular parameters, such as actin dynamics, sensitivity to caffeine (Valster and Hepler, 1997), and microtubule dynamics (Seguí-Simarro et al, 2008), although an exact correlation warrants experimental proof.…”
Section: Discussionmentioning
confidence: 99%
“…E-mail annemie. emons@algem.pcm.wau.nl; fax 31 -31 7-485005.ing spindle-interzone elements, the actin filaments seem to originate de novo as two opposing groups, each initially associated with the surface of the re-forming daughter nuclei (Zhang et al, 1993;Valster and Hepler, 1997).Although it is clear that actin filaments are associated with the phragmoplast, it is much less clear how they participate in cell plate formation. One possibility is that, together with a myosin motor, they cause the transport of Golgi vesicles, which contain cell wall precursors, to the edge of the developing cell plate.…”
mentioning
confidence: 98%
“…Evidence for a role of actin filaments in cell plate positioning comes from observations showing that cytochalasin can prevent proper alignment of the developing cell plate (Palevitz and Hepler, 1974; Palevitz, 1987;Schmit and Lambert, 1988;Mineyuki and Gunning, 1990). In addition, recent evidence reveals that actin filaments form bridging structures between the phragmoplast 181 6The Plant Cell of the centrifugally expanding cell plate and cortical actin filaments (Valster and Hepler, 1997).Although previous pharmalogical studies with cytochalasins have shown that actin filaments are required for normal cell plate formation (Palevitz and Hepler, 1974; Palevitz, 1987;Schmit and Lambert, 1988;Mineyuki and Gunning, 1990), the application of this reagent is likely to underestimate the importance of actin in cytokinesis. For example, cytochalasin does not completely depolymerize actin filaments, and in some systems, it may even promote polymerization and bundling of these cytoplasmic elements (Tang et al, 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A polarized mode of cytokinesis is observed in vacuolate Arabidopsis cells, which was suggested to involve short-range interactions between the phragmoplast and the plasma membrane [54]. These 'interactions' are presumably mediated via strands of MTs and also, possibly, actin (Figure 2) [55][56][57]. Direct sightings of connective cytoskeletal strands are difficult because there might be only a few of them, which are likely to be highly mobile or might occur only at discrete areas of the cortical division zone as suggested by Cutler and Ehrhardt [54].…”
Section: Vesicle Trafficking and The Cortical Division Zonementioning
confidence: 99%